The Relationship of Self Efficacy Breastfeeding with Exclusive Breastfeeding in the Working Area of the Bunut Health Center in 2025 - Winda Harini; Mirna Desiyanti; Nabella Nabella (International Journal Of Health Science, 2026)
Breast milk is the best source of nutrition for infants from birth, providing complete nutrients essential for growth, brain development, and immunity. Exclusive breastfeeding during the first six months has been proven to reduce the risk of infectious diseases, prevent malnutrition, and decrease child mortality rates. However, exclusive breastfeeding coverage remains suboptimal. Globally, the breastfeeding coverage rate in 2024 reached only 48%, while in Indonesia it was 67.96%, which is still far below the national target of 80%. In Lampung Province, coverage was 76.40%, while in the Bunut Health Center area, it was only 60%. A preliminary study showed that only 30% of mothers practiced exclusive breastfeeding, while 70% did not, mainly due to perceived low milk production and frequent infant fussiness. The aim of this study was to determine the relationship between Breastfeeding Self-efficacy and Exclusive Breastfeeding practices. This research employed a quantitative analytic design with a cohort approach. The population included all 34 breastfeeding mothers with infants aged five months in the Bunut Health Center working area, with the sample selected using total sampling. The study was conducted in July–August 2025. Data were collected using questionnaires and analyzed bivariately with the chi-square test. The results showed that 18 mothers (52.9%) had high breastfeeding self-efficacy, and 22 respondents (64.7%) did not practice exclusive breastfeeding. A significant relationship was found between breastfeeding self-efficacy and exclusive breastfeeding (p-value = 0.024; OR = 8,750). Suggestions for mothers are to increase their breastfeeding confidence by actively participating in breastfeeding support groups and involving their husbands for support. For the Health Center, it is recommended to optimize lactation counseling focused on psychological empowerment (self-efficacy) and establish peer support groups to share breastfeeding success stories.